ANALISIS KOMPARASI POTENSI KEBANGKRUTAN PADA PERUSAHAAN HUAWEI TECHNOLOGIES DENGAN METODE ALTMAN Z – SCORE DAN ZMIJEWSKI X – SCORE - Desy Ayu Ramadhani; Arief Nurdiannova Qurochman (MAPAN: Jurnal Manajemen Akuntansi Palapa Nusantara, 2020)
The purpose of this study is to know potential bankruptcy by using Altman Z-Score and Zmijewski X-Score method on Huawei Technologies company in 2014 – 2019 period. This study used two methods of bankruptcy prediction, they are Altman Z-Score and Zmijewski X-Score. The data used is the annual financial report of the Huawei Corporation at the website www. Investing.com. the study uses quantitative research and samples used in this study the Huawei company’s financial report period 2014-2019. The choice of that span is based on the opinion that, at this time, restrictions on huawei products are imposed by the United States Government. The study shows that since 2014-2019 after blocking of Huawei in America was healthy or did not have the potential for bankruptcy using the Altman Z-Score and Zmijewski X-Score.Keywords: Potential Bankruptcy, Method of Altman Z-Score, Method of Zmijewski X-Score